2017
DOI: 10.3126/on.v15i1-2.18791
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental regulated water temperature variations on survival, growth performance and haematology of African catfish, Clarias gariepinus

Abstract: A 56 day study was carried out to evaluate effect of temperature changes on survival, growth performance and haematology of Clarias gariepinus fingerlings fed housefly maggot meal (magmeal) diet. Ninety (90) Clarias gariepinus fingerlings, (initial mean weight 4.33±0.03g) were subjected to different environmental regulated temperature conditions in three locations (laboratory, outdoor, greenhouse). The observed average temperature was 26.53±0.01°C, 26.06±0.01°C and 31.52±0.00°C for laboratory, outdoor, greenho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
2
13
1
Order By: Relevance
“…Similar to our study, numerous other freshwater fish species displayed great improvement in FCR and FCE as temperature increased [ 29 , 30 , 31 , 32 ]. However, there were two major concerns that arose from the FCR and FCE acquired in our study; (1) the growth performance parameters observed in our study did not match the feed utilization data obtained (no significant difference in growth between treatments), and (2) the value of FCR obtained in our study was noticeably poorer as compared to FCR values obtained in other studies [ 20 , 33 , 34 ]. The calculations for both FCR and FCE were complicated by the fact that mortality (induced by cannibalism) occurred in all treatments except 26 °C throughout the experimentation period, resulting in data variability.…”
Section: Results and Remarkscontrasting
confidence: 94%
See 3 more Smart Citations
“…Similar to our study, numerous other freshwater fish species displayed great improvement in FCR and FCE as temperature increased [ 29 , 30 , 31 , 32 ]. However, there were two major concerns that arose from the FCR and FCE acquired in our study; (1) the growth performance parameters observed in our study did not match the feed utilization data obtained (no significant difference in growth between treatments), and (2) the value of FCR obtained in our study was noticeably poorer as compared to FCR values obtained in other studies [ 20 , 33 , 34 ]. The calculations for both FCR and FCE were complicated by the fact that mortality (induced by cannibalism) occurred in all treatments except 26 °C throughout the experimentation period, resulting in data variability.…”
Section: Results and Remarkscontrasting
confidence: 94%
“…Initial weight (W i ) in all treatments showed no significant difference ( p > 0.05), reflecting on the homogeneity in fish weight at the beginning of the experiment. This complements several previous observations which agreed that the optimal temperature for the best growth of African catfish lies between 26 and 32 °C [ 20 , 21 , 25 , 26 ].…”
Section: Results and Remarkssupporting
confidence: 90%
See 2 more Smart Citations
“…African catfish ( Clarias gariepinus ) can perform adequately if the water temperature is around 25–28 °C (Andrews and Stickney, 1972 ; Ogunji and Awoke, 2017 ). However, high temperatures adversely impact oxygen availability in the water (Buentello et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%